THE EFFECT OF MANDALA PATTERN COLORING ACTIVITY ON THE ANXIETY LEVEL OF STUDENTS IN DIRGAHAYU NURSING ACADEMY SAMARINDA - Kristina Kristina (NurseLine Journal, 2017)
Nursing education system in Indonesia based on the competency-based curriculum is learning experiences that require nursing students to study both in campus and in health services areas. It can cause anxiety to the students. If a student experiences an ongoing increase in anxiety, it can cause negative effects so that students' learning motivation becomes decreased. The purpose of this study was to determine the effect of mandala pattern coloring activity on the level of anxiety among nursing students in Dirgahayu Nursing Academy, Samarinda. This study was pre-experiment research with one group pre-test and post-test design. The population of this study was students in Dirgahayu Nursing Academy, Samarinda and the sample was students in 4th semester. The sampling technique used in this study was purposive sampling. Hamilton Rating Scale for Anxiety (HARS) was applied to measure anxiety level. Data were analyzed by using paired-samples t-test. The results of data analysis using Microsoft Excel 2010 with t-test formula showed p value: 0.004, indicating a significant difference in anxiety level before and after the mandala pattern coloring activity. Mandala pattern coloring activities can be used as an appropriate activity to reduce anxiety..